Effect of biological control factors acting on population dynamics parameters insect of Sesamia cretica Led. (Noctuidae:Lepidoptera) Tow varities on corn Zea mays L in Ninavah providenceEffect of biological control factors acting on population dynamics parameters insect of Sesamia cretica Led. (Noctuidae:Lepidoptera) Tow varities on corn Zea mays L in Ninavah providence (NTU Journal of Agriculture and Veterinary Science, 2025)
The study was conducted under field conditions during the autumn season of the year 2023. A detailed account was given of the population dynamics of the corn stalk borer Sesamia cretica Led. (Noctuidae:Lepidoptera) infested two Varieties of corn Zia mays (Zwan and Samoray) in three regions belong to Ninavah provedence: Mosul city, Rabiaa and Nimrod districts. To investigate major mortality factors that are responsible for the change of S. cretica on corn were identified as density-dependent factors including predation and unknown factors which are independent. Predation by Anthocoris spp., green lacewings (Chrysopela spp.), and ladybugs (Coccinella semptempunctat and C. undecimpunctata) are a significant contributor to death. Birds also played a major role in  predation of larvae and pupae that fed on tissue. Results showed that photoperiod and normal female mortality rate played an important role in reducing the pest level. Results revealed that S. cretica population were subjected to great biotic and abiotic mortality factors which played a major role in the destruction of their mature and immature stages. The trend index of the second generations was always below 1% , while for the first generations were above 1% .